Berry anthocyanin-based films in smart food packaging: A mini-review. (December 2022) - Neves, Dina; Andrade, Paula B.; Videira, Romeu A.; de Freitas, Victor; Cruz, Luís
Abstract: Smart packaging is an emergent technology in food industry, incorporating intelligent and active materials capable to detect spoilage in real-time and extend the food shelf-life. The current trend is to create sustainable packs made of biopolymers and extracts of anthocyanins, the polyphenol pigments of plants endowed with antioxidant activity and pH-responsive properties to monitor microbial food deterioration. Indeed, a large number of articles were published about anthocyanin films over the last decade, nevertheless, none study categorizes the films by the type of source of anthocyanin extracts (vegetables, fruits, flowers). Thus, this review summarizes the state-of-the-art of smart packaging films based on anthocyanin extracts from berries, namely, their preparation, characterization, and validation in real systems. Various berries from Ericaceae (blueberry), Rosaceae (blackberry), and other families (mulberry) have been integrated into food films, mostly by casting technique. The films are described in terms of morphology, mechanical, and physicochemical features, and validated as pH intelligent indicators of food freshness, or active packs against lipid oxidation. Some anthocyanin films emerge like "dual-functional packaging", but stability studies (temperature, light) are required to their industrial scale-up nowadays. Graphical abstract: Image 1 Highlights: Food packaging films based on anthocyanin extracts from berries. Films reviewed pursuant to the taxonomic family of berry-producing plants. Films were prepared by casting and validated as pH indicators of food spoilage. Future outlook over their intelligent and active applications in industry.